The Limits of Equality The Intersectionality of Gender and Sexuality in Spanish Policy Making - Méndez, Raquel Platero (Kvinder, Køn & Forskning, 2007)
In the course of less than forty years, the Spanish political and cultural scenario has changed drastically, particularly in relation to civil rights. Social movements, especially feminist and LGBT (Lesbian, Gay, Bisexual, Transgender) organizations, have been successful in putting demands on the political agenda that have translated into gender equality, same-sex and transgender laws. Looking at definitions of equality, this article explores the implications of some postmodern theories that promote the analysis of political intersectionality for some of the recent laws that are presented as progressive and transformative in Spanish policy making. The analysis will explore two case studies: samesex marriage and equality policy law texts, discussing the conception of intersectionality and equality. In addition, the definition of the feminist political strategy in which these policies are framed is addressed. Both case studies show that the policies are conceptualized within a liberal and assimilationist framework, since neither the male norm nor the sexual order is profoundly questioned.